"Modi locupletandi exempla": "Progymnasmata" y teorías sobre la dilatación narrativa del "exemplum" (1997)
The modi locupletandi exempla (c. 1499) by Erasmus are the first concrete theory about the development of the exemplum. It had a big influence on the Spanish Rhetorics of the Renaissance. One of its fundamental sources are the classical Progymnasmata, specially the models of the narratiuncula, fabula and chria. In fact, those models were up to the Sixteenth Century the ways to th at job of development of the exemplum and so they continued even after of the birth of the modi locupletandi exempla.
Keywords: Erasmus, Desiderius, -- 1467-1536; Crítica literaria